Brain size predicts behavioural plasticity in guppies (Poecilia reticulata): An experiment. (21st December 2018) - Herczeg, Gábor; Urszán, Tamás J.; Orf, Stephanie; Nagy, Gergely; Kotrschal, Alexander; Kolm, Niclas
Abstract: Understanding how animal personality (consistent between‐individual behavioural differences) arises has become a central topic in behavioural sciences. This endeavour is complicated by the fact that not only the mean behaviour of individuals (behavioural type) but also the strength of their reaction to environmental change (behavioural plasticity) varies consistently. Personality and cognitive abilities are linked, and we suggest that behavioural plasticity could also be explained by differences in brain size (a proxy for cognitive abilities), since accurate decisions are likely essential to make behavioural plasticity beneficial. We test this idea in guppies ( Poecilia reticulata ), artificially selected for large and small brain size, which show clear cognitive differences between selection lines. To test whether those lines differed in behavioural plasticity, we reared them in groups in structurally enriched environments and then placed adults individually into empty tanks, where we presented them daily with visual predator cues and monitored their behaviour for 20 days with video‐aided motion tracking. We found that individuals differed consistently in activity and risk‐taking, as well as in behavioural plasticity. In activity, only the large‐brained lines demonstrated habituation (increased activity) to the new environment, whereas in risk‐taking, we found sensitization (decreased risk‐taking) in both brain size lines. We conclude that brain size, potentially via increasing cognitive abilities, may increase behavioural plasticity, which in turn can improve habituation to novel environments. However, the effects seem to be behaviour‐specific. Our results suggest that brain size likely explains some of the variation in behavioural plasticity found at the intraspecific level.